DAMPAK KNOWLEDGE MANAGEMENT PRACTICES TERHADAP KINERJA DOSEN UNIVERSITAS MEDAN DAN PADANG - Anna Kridaningsih (Media Mahardhika, 2020)
This research explores the influence of knowledge management methods on the work of lecturers at bauchi and Gombe States universities. In this study, knowledge management practices were established; knowledge generation, knowledge acquisition, knowledge sharing and knowledge storage. The research is based on cross-sectional designs and surveys. The survey was conducted at four (4) research institutes distributed to college academics. A total of 325 surveys were distributed and 265 were returned with a response rate of 81.5%. The validity and reliability of the data is reviewed through the Social Science Statistics Package (SPSS) and all structures are met. Multiple regression analysis is used to evaluate hypotheses. The results of this study show that all information management structures are positively related to the success of lecturers. Generation and acquisition of knowledge as the main influence on the output of established lecturers. This paper supports the value of knowledge management strategies to improve overall efficiency. Discussion of research results is discussed and sponsored. Among other things, this paper recommends a holistic approach in all aspects of knowledge management practices and features that influence knowledge management achievement. In conclusion, this study highlights and recognizes the influence of knowledge management practices on teacher success and thus helps policymakers to gain comprehensive insight into the impact of knowledge management practices in the context of universities in Nigeria.